The Blackberry - Peter C. Andersen; Timothy E. Crocker (EDIS, 2011)
Learn about traditional and promising new cultivars and how to grow them the home landscape. This revised 10-page fact sheet was written by Peter C. Andersen and Timothy E. Crocker, and published by the UF Department of Horticultural Sciences, May 2011.